Rotating bending fatigue behaviour of a Ni3Al-based single crystal alloy IC6SX at 760°C. (May 2015) - Jiang, L. W.; Wu, M. L.; Li, S. S.; Han, Y. F.
<x content-type="archive" xml:space="preserve">Abstract</x> The high cycle fatigue behaviour at 760°C of a Ni3Al-based single crystal alloy IC6SX has been studied in the present investigation. The specimens for the fatigue tests were prepared by screw selection crystal method in a directional solidification furnace. The rotating bending fatigue tests of the specimens was carried out at the temperature of 760°C in air, the stress ratio of R (σmax/σmin) was − 1, and the rotating speed of the fatigue tests was 6500 r min− 1 (108 Hz). The stress–fatigue life cycle (S − Nf) curve was obtained based on the fatigue tests, and the fracture surfaces were examined using scanning electron microscopy (SEM). The results showed that the fatigue cracks initiated from the surface defects of the specimens and the cracks propagated along the (111) crystal plane. The fatigue fracture was composed of three different characteristic regions corresponding to the three fatigue stages, including fatigue crack initiation stage, steady-state propagation stage and the fast propagation stage. The research results also showed that the rotating bending fatigue performance of alloy IC6SX is superior to that of the second-generation single crystal nickel-based superalloys containing 3 wt-% Re.